1984
DOI: 10.1016/0304-3959(84)90111-8
|View full text |Cite
|
Sign up to set email alerts
|

Discharge pattern of afferent fibers from a neuroma

Abstract: Discharge properties of afferent units from experimentally produced stump neuromata in the superficial peroneal nerve of the cat hind limb were investigated electrophysiologically. The superficial peroneal nerves were cut and ligated 6-245 days before the experiments. Myelinated and chiefly unmyelinated axons were analyzed. The following results were obtained: (1) 3.9 +/- 3% (mean +/- S.D.) of axons from early neuromata (days 6-27) and 13.4 +/- 10.7% of axons from old neuromata (more than 50 days after nerve s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
2

Year Published

1988
1988
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(63 citation statements)
references
References 36 publications
3
58
0
2
Order By: Relevance
“…Similar effects are also seen after activating postganglionic sympathetic fibres ending in the neuroma by electrical stimulation of the lumbar sympathetic trunk (Blumberg & Janig, 1981;Devor & Janig, 1981;Korenman & Devor, 1981;Blumberg & Janig, 1984;Habler, Janig & Koltzenburg, 1987). Although most of these observations were made on myelinated neuroma fibres, Habler et al (1987) have shown unmyelinated ones respond to such stimulation as well.…”
Section: Interactions Between Fibresmentioning
confidence: 68%
See 3 more Smart Citations
“…Similar effects are also seen after activating postganglionic sympathetic fibres ending in the neuroma by electrical stimulation of the lumbar sympathetic trunk (Blumberg & Janig, 1981;Devor & Janig, 1981;Korenman & Devor, 1981;Blumberg & Janig, 1984;Habler, Janig & Koltzenburg, 1987). Although most of these observations were made on myelinated neuroma fibres, Habler et al (1987) have shown unmyelinated ones respond to such stimulation as well.…”
Section: Interactions Between Fibresmentioning
confidence: 68%
“…There are some differences in opinion as to how common are all these events. The incidence varies with time after nerve injury (Govrin-Lippmann & Devor, 1978;Blumberg & Janig, 1984), between different strains of rat -it being uncommonly high in the Wistar-derived Sabra strain - (Devor, Inbal & Govrin-Lippmann, 1982;Burchiel & Russell, 1987), and between species (Blumberg & Janig, 184;Meyer, Raja & Campbell, 1985). There is also the suggestion that some pharmacological agents used routinely in the conduct of experiments could be a source of variation (Burchiel & Russell, 1987).…”
Section: Neuroma Dischargementioning
confidence: 99%
See 2 more Smart Citations
“…Neuroma is not systematically associated with acute or chronic pain. Pain, caused by abnormal spontaneous neuroma's activity or to increased sensibility of it (Swanson, 1961;Scadding, 1981;Blumberg and Jä nig, 1984), is influenced by the healing process quality, itself relying on the type of operation, the age and the quantity of tissue removed (horse: Said and Khami, 1984;poultry: Gentle et al, 1995;Lunam et al, 1996). Skin adhesion subsequent to tail docking has also been observed in docked dogs (Carr, 1979).…”
Section: Cosmetic Aspectsmentioning
confidence: 99%